An Analysis on Slang Words in Movie “Agak Laen’’ - Pasaribu, Eka; Sohnata Hutauruk, Bertaria; Silalahi, Dumaris Elseria (Universitas Pahlawan Tuanku Tambusai, 2024)
This research examines the slang words used in the utterances of the film